TiO₂ photoanode for transparent dye sensitised solar cells - Husain Suhayla, Alaa A. F (2018)
The Photovoltaic (PV) cell is the main component used to transfer photons directly into electricity. Traditionally PV technologies were categorized as mono-crystalline, polycrystalline and amorphous, which can use a myriad of inorganic semiconductor materials, the most common being silicon. The economic drive to make solar cells more cost effective and efficient has driven developments with many different deposition technologies including dipping, plating, thick film and thin film. However today a new Organic PV technology is emerging giving rise to new interesting developments. The challenge of the current Photovoltaic is the big space it utilize to install solar panels system to support building or and application. This space is not available specially in the city where so many applications requires solar energy. This research is interested in the new generation of solar cells and specifically Transparent Photo-Voltaic cells (TPV). Transparent solar cells can better utilize space and provide power by absorbing and utilizing unwanted light energy from windows in buildings and automobiles. TPV will make use of existing glass-covered areas to generate electricity leading to a better use of architectural space. There are several TPV technologies being researched using different materials and processes, which aim to achieve a high transparency and high electrical performance. However, few of these technologies reached the market and most of the researches are working on developing and improving this application. This research looks at the different technologies and compares, methods and materials used from a performance, aesthetic and financial perspective. In this project the main focus is on the photoanode of Dye Sensitized Solar Cell (DSSC) to be transparent. Through using 3 types of deposition (screen printing, spin coating, Electrophoretic technique) and different structure of TiO2 (nanotubes, transparent paste) the transparency to efficiency ratio can be controlled. Titanium dioxide is used as a photoanode with different structure and a selected dye with high average transmission in the visible region. The total average transparency achieved is 75% in the visible region and the efficiency is 3.2% using solar cell simulator.